The formation of personal judgment in practical affairs: An epistemological view - Lombo, José Angel (Church, Communication and Culture, 2022)
In our present cultural situation, we observe a growing expansion of information together with a proliferation of opinions and interpretations. This situation has been intensified by the health emergency caused by the Covid-19 virus. Our study aims to provide the keys for the formation of personal judgment in the practical field, so that it can indirectly serve as guidance for the management of information related to the pandemic. We will attempt to illustrate, first, the specificity of practical knowledge, describing its sources and conditions, as well as the scope of practical truth, which such judgment allows us to reach. Secondly, we will point out the factors that positively and negatively influence personal judgment. On the one hand, we will indicate some external elements that hinder or prevent access to information, such as misinformation, disinformation and fake news. On the other hand, we will focus on the internal dispositions of practical judgment, particularly the intellectual and moral virtues. In this context, we will deal in greater detail with prudence as a dianoetic virtue. We will conclude by pointing out the importance of the virtues in achieving critical thinking, and the importance of critical thinking in building stable access to information.